ICAR-DARE steered successfully G20 Meeting of Agricultural Chief Scientists (MACS) - Mishra, J P; Mandal, Bikas; Pathak, Himanshu (Indian Farming, 2023)
The G20 works to address major global issues related to food security, nutrition, economy, financial stability, climate change adaptation and mitigation, and sustainable development. The Meeting of Agricultural Chief Scientists (MACS) in G20 is a scientific track of information exchange on the issues of utmost relevance and crucial needs for joint action in the future. The MACS 2023 has been steered by DARE-ICAR and was held with the theme of ‘Sustainable Agriculture and Food Systems for Healthy People and Planet’. The discussions on issues of relevance for food security especially in the context of International Year of Millets, resilience to crisis through climate resilient agriculture and One Health approach, emerging issues e.g. digital agriculture and public-private partnerships for R&D were held. The meeting specifically featured Millets and Other Ancient Grains International Research Initiative (MAHARISHI) and was accepted by all member countries with emphasis on millets based local food system for agrobiodiversity, food and nutrition security.